EXPERIMENTAL ANIMAL MODEL OF THYROID DYSFYNCTION- HYPERTHYROIDISM - Stojkovska, Natasha; Manevska, Nevena; Makazlieva, Tanja; Tasheva, Ljubica; Tripunoski, Toni; Stojanoski, Sinisa; Paunkoska, Anamarija; Kostadinova-Petrova, Irena (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
To establish an experimental animal model of impaired function of the thyroid gland – hyperthyroidism. Thyroid dysfunction (hypothyroidism, hyperthyroidism) is classified in the group of non-communicable diseases with high incidence and prevalence. The disturbed function of the thyroid gland reflects in the metabolic processes of organs, tissues and at cellular level. Twenty Wistar rats (10 males - 350 ± 40 gr and 10 females - 320 ± 40 gr), with an average age of 7 months, were analyzed in the period of 2 months (treated for 1 month with pharmacological doses of L-Thyroxin 15mg / 100g body mass in the drinking water and 1 following month without treatment). The second group of 10 Wistar rats - (5 males and 5 females) did not recieve L-Thyroxin and this was the control group used to obtain normal morphometric and biochemical parameters. Between the mean values ​​of FT4 and FT3 at the beginning, at the intersection and at the end of the study, there were statistically significant differences with increased levels of thyroid hormones at the cross section and no statistically significant difference of thyroid hormone levels between the beginning and the end of the examination in the group of rats treated with L-Thyroxin. No statistically significant differences were detected in the control group of rats. Experimental animal model of impaired function of the thyroid gland – hyperthyroidism using Wistar rats as subjects was successfully established. Key words: hyperthyroidism; thyroid dysfunction; thyroid hormones; Wistar rats.